2021
DOI: 10.5871/bacop26/9780856726606.001
|View full text |Cite
|
Sign up to set email alerts
|

Young People and Climate Change

Abstract: Why young people and climate change? Key climate change-related livelihood challenges for young people Young people's input Conclusion and recommendations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…They are more prone to trauma which, especially in early childhood, adds gravity to the expectation of future chaos [20]. Moreover, they are the weakest part of the population (especially in developing countries) due to fewer personal resources, low income, minimal work experience, and lack of professional authority [38,41]. The youth are mainly depicted as fierce activists, adultified children, innocent victims, and ultimate saviors [42].…”
Section: Vulnerable Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…They are more prone to trauma which, especially in early childhood, adds gravity to the expectation of future chaos [20]. Moreover, they are the weakest part of the population (especially in developing countries) due to fewer personal resources, low income, minimal work experience, and lack of professional authority [38,41]. The youth are mainly depicted as fierce activists, adultified children, innocent victims, and ultimate saviors [42].…”
Section: Vulnerable Groupsmentioning
confidence: 99%
“…On the one hand, climate change anxiety and the lack of opportunities to address environmental issues are thought to increase concerns about the future, to be detrimental to wellbeing and to contribute to clinical anxiety and depression in emerging adults. On the other hand, engaging in individual and collective action might be protective against mental symptoms [41,46], with many young people taking part in awareness campaigns and protest movements. Seen from this perspective, younger generations should not be excluded from policy dialogues in order for their mental resilience to thrive.…”
Section: Vulnerable Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the multiple crises in the recent years, young people have been much at the centre of public and scholarly attention as a generation of being particularly affected. Described, for instance, as 'Youth in an Age of Lost Opportunity' (World Economic Forum, 2021: 39) or a generation 'in permanent crisis mode' (Schnetzer and Hurrelmann, 2022) research has shown what impact the 2008 economic crisis (Coppola and O´Higgins, 2016;Schoon and Bynner, 2017), the Covid-19 pandemic (Gittings et al, 2021; for an overview see Li and Yu, 2022) and the increasingly tangible climate crisis (Barford et al, 2021) have on young people, their everyday lives and future (perspectives). In addition to studies on (more limited) access to the labour and housing market (Antonucci et al, 2014;France, 2016) and the (prolonged) transition into adulthood (Gentile, 2014;Moreno Mínguez et al, 2012), researchers increasingly raised the question of how these profound changes affect young people's narratives and imaginaries (Benedicto et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Young people will face the consequences of climate change throughout their lives to a greater degree than previous generations [1]. Given the high stakes of inaction on climate change, it has never been more urgent to ensure that university students learn about climate change from broad, interdisciplinary perspectives that include connections to the social determinants of health and social issues more broadly [2,3].…”
Section: Introductionmentioning
confidence: 99%